Perception of Infant Feeding among Urban Educated Women - Masoom, Ahsan Kabir; Shameem, Md; Jahan, Jesmin; Bhuiyan, A N M Nurul Haque; Islam, Md Tariqul; Khan, Nabila Zohra; Tauhid, Syed Ahsan; Rahman, Lutfor (Sir Salimullah Medical College Journal, 2023)
Introduction: Despite of high prevalence of breast feeding practices among mothers, infant feeding pattern is not ideal in our country. Short duration of exclusive breast feeding and inappropriate feeding for newborn and infant are common in both urban and rural areas of Bangladesh. Objectives: To explore the perceptions on breastmilk, pre lacteal feeding, complementary feeding and infant feeding among medical and non-medical female students of urban area and to compare their perceptions. Materials and Methods: This cross sectional study was done at Bangladesh Medical College (BMC), Dhanmondi, Dhaka and Hazrat Shah Ali Women University College (HSAWUC), Mirpur, Dhaka from December 2015 to May 2016 and study populations were 100 of which 50 from female medical students of BMC and 50 from female non-medical students of HSAWUC. Data were collected by random sampling as per inclusion and exclusion criteria. Data was compiled manually and analyzed by statistical package for social sciences (SPSS) version 22. Results: Majority of study population were unmarried (88%), most of them were in 21-25 years age group (77%) and a high number among them had crossed higher secondary school level (84%). Comparison of perceptions between medical and non-medical students students of both institutions regarding knowledge of first feed of a newborn, pre lacteal feeds and its importance; time of initiation of breast feeding and harmful effect of bottle feeding showed differences which were statistically significant (P<0.05). The female medical students had relatively better perceptions regarding infant feeding. Conclusions: Although perceptions on infant feeding were more correct among medical students, incorrect perceptions on infant feeding still present in both medical and nonmedical students which is alarming. Sir Salimullah Med Coll J 2023; 31: 86-93